Investasi Digital Reksa Dana dengan Model Unified Theory Acceptance and Use of Technology (UTAUT) Pada Generasi Y dan Z - Yudhita Valen Prasarry; Reagen Yohanes Sayoga; Frihardina Marsintauli; Dessy Handayani (JURNAL ILMIAH MANAJEMEN & BISNIS, 2023)
Purpose –  This research is to determine the factors influencing investors' intention to use investment applications among generations Y and Z.Method – The sampling technique uses purposive sampling to obtain 294 samples of digital investment users in Indonesia. Data was collected online and analysed using structural equation modelling (SEM) based on partial least squares (PLS) components or variants. Results – The study’s results show that performance expectations, effort expectations, social influence, facility conditions, hedonic motivation, and utilitarian motivation are known to have a significant positive effect on behavioural intentions. Furthermore, behavioural intentions have a significant influence on user behaviour.Originality (novelty) – The model used to measure intention to accept digital investment uses the UTAUT model by adding two main factors related to behavioural purposes: hedonic and utilitarian motivation.Implications –  Investment business players are competing to create investment applications that are safe and friendly for beginners to operate, even though there are still many people who are reluctant to invest online because they are still unsure about the legality and security reasons. It is important to know the factors that can stimulate the intention to use investment applications by investors among generations Y and Z. The choice of generations Y and Z is because these two generations were born at a time when new technologies were emerging